Influence of Soil-Structure Interaction on the Seismic Response of the Structure on Mat Foundation - G. D. Awchat; A. S. Monde (Civil Engineering Journal, 2021)
The disasters that occur due to seismic activities not only affect the structure but also soil beneath it. Neglecting the effect of Soil-Structure Interaction (SSI) in design leads to unsafe design. This paper focuses on the behavior of the structure under El-Centro earthquake considering soil-structure interaction (SSI). Seismic response of G+10 storied building in various seismic zones of India is obtained using Time-history method. The direct approach i.e., finite element analysis is used to analyze effect of SSI. The model with mat foundation and soil is compared with fixed base model in SAP 2000 v.20. The behavior of the structure is studied by parameters like inter-storey drift ratio, lateral storey displacements, response spectrum curves for spectral acceleration and spectral velocity for various damping and time period of different seismic zones of India. The parameter like inter-storey drift ratio can determine safety of the structures. From inter-storey drift ratios, the buildings in zone IV and zone V were found to be unsafe. The lateral storey drift was found to increase by 47-87% considering SSI in zone II and 60-95% considering SSI in Zone II, IV and V. It also increased with increase in storey number. The spectral acceleration, spectral velocity and time period increased by considering effects of SSI in each seismic zone. The spectral acceleration and spectral velocity found to decrease with increase in damping and increase in seismic zones from zone II to V. Further to reduce the effect of SSI the structures can be equipped with base isolators and various types of dampers. It is clear that from zone III to V, SSI should be included for structures on soft soil and for retrofitting of the structure. Some experimental studies can further be performed and the numerical modelling can include parameters like P-delta, angle of incidence of ground motions and various structural systems can be implemented in this study. Doi: 10.28991/cej-2021-03091752 Full Text: PDF